Advanced part design method for springback minimization of stamped sheet metal car body components. Issue 1 (1st May 2022) - Birkert, A; Hartmann, B; Nowack, M; Petker, A; Scholle, M; Zimmermann, P; Kraft, T.
Abstract: The requirements for high-strength and low-weight car body structures prove challenging for the stamping process and cause growing problems with the elastic springback. Compensation approaches such as the geometrical adjustment of the stamping dies by the amount of and in opposite direction to the springback can be an effective solution in many cases. However, this approach can only lead to satisfactory results if the scatter of the springback is considered, controlled and in the best case reduced. The reduction of the scatter can be provoked by adaption of the part design. Therefore, different methods such as the topology optimization method, the so-called line-of-force method and shape optimization can be applied. In the present work an advanced topology optimization method is suggested. Based on the decomposition of the springback deformation into membrane and bending components, the most efficient optimization of the part design is found relying on unconventional topology optimization. For the proposed adapted topology optimization approach the excellent results are also confirmed when applied to the industry-relevant case of a truck rear panel.